2005
DOI: 10.1073/pnas.0508752102
|View full text |Cite
|
Sign up to set email alerts
|

A schizophrenia-related sensorimotor deficit links α3-containing GABA A receptors to a dopamine hyperfunction

Abstract: Overactivity of the dopaminergic system in the brain is considered to be a contributing factor to the development and symptomatology of schizophrenia. Therefore, the GABAergic control of dopamine functions was assessed by disrupting the gene encoding the ␣3 subunit of the GABAA receptor. ␣3 knockout (␣3KO) mice exhibited neither an obvious developmental defect nor apparent morphological brain abnormalities, and there was no evidence for compensatory up-regulation of other major GABA A-receptor subunits. Anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(157 citation statements)
references
References 41 publications
7
148
0
1
Order By: Relevance
“…Knockout studies have shown this subunit to be involved in sensorimotor signaling and a hyperdopaminergic phenotype, which has been suggested to be related to schizophrenia. 39 The correlation of the expression of these genes in the PFC of rats with high body weight indicates PFC serotonergic and adrenergic signaling to be affected in these animals with concurrent effects on monoaminergic receptor expression and subsequent effects on GABA-receptor gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout studies have shown this subunit to be involved in sensorimotor signaling and a hyperdopaminergic phenotype, which has been suggested to be related to schizophrenia. 39 The correlation of the expression of these genes in the PFC of rats with high body weight indicates PFC serotonergic and adrenergic signaling to be affected in these animals with concurrent effects on monoaminergic receptor expression and subsequent effects on GABA-receptor gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…EAE was induced in adult offspring of control or poly-I:C-treated rats by immunization with MBP 68-86 emulsified in CFA, 29 and clinical symptoms of encephalomyelitis were monitored daily. The offspring of poly-I:C-treated rats showed a delayed onset and a shorter duration of EAE symptoms following MBP [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] vaccination, compared to the controls (Table 1b). These results supported our contention that immune activation during pregnancy is associated with reduced immune response to brain antigens in the offspring.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, adult offspring of the poly-I:Ctreated rats showed a reduction in PPI compared to the progeny of saline-treated animals (Supplementary Figure 1). To measure alterations in immunity to brain-specific antigens in the poly-I:C-affected offspring, we vaccinated female and male offspring at adulthood with the myelin basic protein (MBP)-derived peptide, MBP 68-86 , a CNS-associated self-antigen known to be the immune-dominant epitope in this strain, 33 and examined lymphocyte proliferation in response to the injected antigen, MBP [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] , as well as to Con-A, a lymphocyte mitogen, or to Ova (an irrelevant antigen). We found, in lymphocytes of the offspring of the poly-I:C-treated animals, a significant reduction in the proliferative response to MBP (Table 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensorimotor gating of the ASR is also subject to regulation by the putative causative agents of PMDD, including steroid hormones and dysregulation of inhibitory neurotransmission. Sensorimotor gating is regulated by GABA A receptors in several relevant brain regions, notably the amygdala and the bed nucleus of the stria terminalis (BNST) Yee et al, 2005;Hauser et al, 2005). Ovarian steroids also appear to influence PPI because women have lower levels of PPI than men (Swerdlow et al, 1993) and because PPI varies across the menstrual cycle in healthy women (Jovanovic et al, 2004;Swerdlow et al, 1997).…”
Section: Introductionmentioning
confidence: 99%